Assessment Status of Learner-centred Learning in Tanzania in the Context of the Competence-based Curriculum - Kitta, S.; Tilya, F. (Papers in Education and Development, 2018)
Learner-centred assessment is a result of a paradigm shift from the teacher-centred approach to the learner-centred approach to teaching. In this shift, assessment is intertwined with learning, whereby various methods are used to collect evidence about students ' learning. In this paradigm shift, feedback plays a substantial role in supporting students ' learning. It serves as a mirror showing students ' understanding of their strengths and weaknesses. When incorporated with suggestions for improvement, feedback can play an important role in motivating students to learn.